Recycling orthodontic brackets the effect of sandblasting on the shear bond strength of rebonded orthodontic brackets - Rivera, Jose Manuel R.
34 non-carious human premolars (17 maxiliary and 17 mandibular), which were stored in normal saline solution within 6 months of the study, were bonded with standard-edgewise brackets (Ormco) and tested for retention prior to and after recycling of the brackets using a sandblasting technique (Danville Engineering). Measurement of shearing strengths using an Instron Machine were performed to observe any possible changes in retentive properties of the brackets. The teeth were preconditioned by the application of adhesive material, followed by scaling and polishing with pumice to remove any visible residual composite. After bonding of the teeth and recording of retentive strengths, the type of bond failure was scored using Adhesive Remnant Index (ARI). The brackets were sandblasted and the same teeth (after scaling and polishing with prumice) were rebonded and tested once more. An increase in retentive strength of 13.6 (p less than 0.001) was observed on the recycled brackets. This was attributed to the greater surface area produced by sandblasting on the brackets base as viewed under the Scanning Electron Microscope (SEM). On the other hand, no statistical difference (p greater than 0.05) was observed with regard to the ARI scores (less than 3) between the bonded and rebonded brackets.